Influencer Marketing and Consumer Decision-Making in Online Retail: A Social Media Perspective (Journal of Advances and Scholarly Researches in Allied Education, 2025)
This study explores the impact of social media marketing on consumer decision-making within the online retail sector. With the growing influence of platforms like Instagram, Facebook, & YouTube, the research investigates whether social media interactions truly affect consumers' buying behaviors. Using a structured online questionnaire, data were collected from 591 respondents who actively engage in online shopping and social media use. The study adopted both exploratory and descriptive research designs. Descriptive statistics analyzed demographic patterns, while chi-square tests examined the relationship between social media engagement and offline purchase intent. Findings reveal that while social media enhances brand visibility & consumer interaction, it does not significantly influence consumers' in-store purchasing decisions based on web-based product research. Variables such as ad clicks, brand page visits, and feedback seeking on social media showed no statistically significant association with offline buying behavior. This research contributes to digital marketing strategies by indicating that while social media is effective for awareness and engagement, its direct impact on offline purchasing is limited. Marketers should consider more targeted and action-driven campaigns to bridge this gap.